Perceived epilepsy-related stigma is linked to the socioeconomic status of the residence - Hohmann, Louisa; Berger, Justus; Kastell, Shirley-Uloma; Holtkamp, Martin (Frontiers in Public Health, 2022)
Purpose: Epilepsy is one of the most common neurological disorders with high costs for the healthcare systems and great suffering for patients. Beyond seizures, psychosocial comorbidities can have detrimental effects on the well-being of people with epilepsy. One source of social stress and reduced quality of life is epilepsy-related stigma that often occurs, e.g., due to public misconceptions or myths. Stigma has individual biological, psychological and social correlates. Moreover, environmental factors like living in remote areas are associated with stigma. However, little is known about the link between the social structure of the residence and stigma in epilepsy. Thus, we investigated the association between the structural socioeconomic status (SES) and perceived stigma in an urban epilepsy population. Methods: This prospective, cross-sectional study examined 226 adult in-patients with epilepsy from Berlin. Multiple regression analyses were performed to check the relationship between structural SES and stigma controlling for individual-level demographic, clinical, psychological and social factors. Continuous social indices (SI) of the districts and neighborhoods (‘SI district’ and ‘SI neighborhood’) of Berlin were used to measure different levels of structural SES. Nonlinear relationships are tested by grouping the SI in quartiles. Results: Both indicators of structural SES were independently linked to stigma (p = .002). For ‘SI district’, we identified a nonlinear relationship with patients from the most deprived quartile feeling less stigmatized compared to those in the second (p <.001) or least deprived quartile (p = .009). Furthermore, more restrictions of daily life (p < .001), unfavorable income (p = .009) and seizure freedom in the past six months (p = .05) were related to increased stigma. A lower ‘SI neighborhood’ was associated with higher stigma (p = .002). Conclusion: Strategies to reduce epilepsy-related stigma need to consider the sociostructural living environment on different regional levels. Unfavorable relations with the immediate living environment may be directly targeted in patient-centered interventions. Nonlinear associations with the structural SES of broader regional levels should be considered in public education programs. Further research is needed to examine possible underlying mechanisms and gain insight into the generalizability of our findings to other populations.